KELIMPAHAN VEGETASI POHON PAKAN LUTUNG JAWA DI TAMAN WISATA ALAM PANANJUNG PANGANDARAN - Eghi Ramdhani (Wanamukti: Jurnal Penelitian Kehutanan, 2021)
The existence of Javan langurs is currently increasingly threatened due to several factors, such as deforestation which causes reduced availability of forage. Taman Wisata Alam (TWA) Pananjung Pangandaran is one of the habitats of Javan langurs and has an abundance of tree diversity and does not yet have data on the abundance of feed types. The objective of research was to determine the abundance of Javan langur food trees in TWA Pananjung Pangandaran. The method used is by modifying the status and abundance category based on the results of vegetation analysis. Javan langur food trees species in TWA Pananjung Pangandaran consist of 30 species from 28 families. The abundance of Javan langur feed in TWA Pananjung Pangandaran at the pole level vegetation there were 3 types which included the category of very much abundance, category of abundance there were 3 types, category of low abundance there were 3 types, and category of very little abundance was found in 2 species. Abundance at the tree level consists of a very large category of 6 species, a large category consisting of 6 species, a low category consisting of 6 species, and a very low category consisting of 5 species.